Recent Advances in Additive Manufacturing and 3D Bioprinting for Organs-On-A-Chip and Microphysiological Systems - Rothbauer, Mario; Eilenberger, Christoph; Spitz, Sarah; Bachmann, Barbara E. M.; Kratz, Sebastian R. A.; Reihs, Eva I.; Windhager, Reinhard; Toegel, Stefan; Ertl, Peter (Frontiers in Bioengineering and Biotechnology, 2022)
The re-creation of physiological cellular microenvironments that truly resemble complex in vivo architectures is the key aspect in the development of advanced in vitro organotypic tissue constructs. Among others, organ-on-a-chip technology has been increasingly used in recent years to create improved models for organs and tissues in human health and disease, because of its ability to provide spatio-temporal control over soluble cues, biophysical signals and biomechanical forces necessary to maintain proper organotypic functions. While media supply and waste removal are controlled by microfluidic channel network the formation of tissue-like architectures in designated micro-structured hydrogel compartments is commonly achieved by cellular self-assembly and intrinsic biological reorganization mechanisms. The recent combination of organ-on-a-chip technology with three-dimensional (3D) bioprinting and additive manufacturing techniques allows for an unprecedented control over tissue structures with the ability to also generate anisotropic constructs as often seen in in vivo tissue architectures. This review highlights progress made in bioprinting applications for organ-on-a-chip technology, and discusses synergies and limitations between organ-on-a-chip technology and 3D bioprinting in the creation of next generation biomimetic in vitro tissue models.